2017
DOI: 10.1016/j.amsu.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

An observational study on the association of nonalcoholic fatty liver disease and metabolic syndrome with gall stone disease requiring cholecystectomy

Abstract: ObjectiveRecognition of Non alcoholic fatty liver disease (NAFLD) and metabolic syndrome in patients with gallstones undergoing laparoscopic or open cholecystectomy, along with it we will also study the life style of patients with gall stones.BackgroundPatients with gallstones have associated NAFLD, with concurrent metabolic syndrome and these ailments share similar factors for example obesity, hypertriglyceridemia and diabetes mellitus. Factors like body mass index, gender, raised lipid levels, use of contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
4
7
0
3
Order By: Relevance
“…Although a few previous studies have shown that the overall prevalence of GSD in patients with NAFLD is not significantly different from those with non-NAFLD, 33 many recent studies suggest a significant association between them. 17,18,[34][35][36][37][38] In our study, there was significant association between GSD and NAFLD (Table 6). NAFLD was present in 62% of GSD patients in one observational study by Ahmed et al, 38 which was higher than our report (42.4%), also the level of LFT in their patients was higher in the NAFLD group, which was similar to our study ( Table 5).…”
Section: Gsdsupporting
confidence: 58%
“…Although a few previous studies have shown that the overall prevalence of GSD in patients with NAFLD is not significantly different from those with non-NAFLD, 33 many recent studies suggest a significant association between them. 17,18,[34][35][36][37][38] In our study, there was significant association between GSD and NAFLD (Table 6). NAFLD was present in 62% of GSD patients in one observational study by Ahmed et al, 38 which was higher than our report (42.4%), also the level of LFT in their patients was higher in the NAFLD group, which was similar to our study ( Table 5).…”
Section: Gsdsupporting
confidence: 58%
“…[ 10 16 ] No associations were found between NAFLD and gallstones in the studies on the US and Korean populations, [ 10 , 13 ] whereas NAFLD was associated with gallstones in the studies on the Pakistani and Taiwanese populations. [ 12 , 15 , 16 ] To the best of our knowledge, only 1 study has been conducted to investigate whether asymptomatic gallstones are related to the risk of NAFLD in a Chinese urban population; that longitudinal cohort study revealed that gallstones are risk factors for NAFLD. However, the correlation between NAFLD and asymptomatic gallstones in a Chinese general population has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, increased denovo lipogenesis is a major driver of hepatic steatosis in the insulin resistance state owing to excessive activation of the lipogenic branch of the insulin signaling pathway in hepatocytes [38,39]. NAFLD is an acquired metabolic disease of the liver, occurring in two phases: (1) triglycerides accumulate in the liver and (2) necrobiotic in ammatory reactions, brosis and cirrhosis take place [40]. Meanwhile, obese individuals are likely to have increased gallbladder volume accompanied by slow gallbladder evacuation and mucosal abnormalities, which are associated with gallstone formation [41].…”
Section: Discussionmentioning
confidence: 99%